2018
DOI: 10.1111/gove.12374
|View full text |Cite
|
Sign up to set email alerts
|

Trust, institutions, and indigenous self‐governance: An exploratory study

Abstract: Trust is important to the institutions that make societies successful. Globally, Indigenous peoples are actively building institutions for self‐governance, but there remains little empirical work on trust in this context. To address this gap, we use a mixed methods approach to explore three levels of trust among individual members from three related, but politically distinct First Nations (Indigenous peoples) in British Columbia, Canada. British Columbia offers a unique and dynamic context to explore trust and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Hence, governance arrangements in low-trust contexts address the collective action problem (Ostrom, 1990) by drawing on people's expectation for cooperative behavior (Fukuyama, 1996;Rothstein, 2005). Moreover, demonstrating that political distrust is compensated with interpersonal trust among the minority members, this article further unfolds recently identified links between low interpersonal trust and low political trust (Nikolakis & Nelson, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Hence, governance arrangements in low-trust contexts address the collective action problem (Ostrom, 1990) by drawing on people's expectation for cooperative behavior (Fukuyama, 1996;Rothstein, 2005). Moreover, demonstrating that political distrust is compensated with interpersonal trust among the minority members, this article further unfolds recently identified links between low interpersonal trust and low political trust (Nikolakis & Nelson, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…The only difference is the slopes and magnitudes of increase for different types of trust. Studies have shown that trust is the glue of societies, economics, and politics, and these outcomes can reciprocally boost the establishment of trust ( Nikolakis and Nelson, 2019 ; Watkins, 2021 ; Zhang et al, 2022 ). Thereby, the trend shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Trust has been theoretically and empirically evidenced as the glue of societies, economics, and politics ( Nikolakis and Nelson, 2019 ). Greater general trust helps generate higher cooperation, a practical contributing factor to social, institutional, and political stability and economic efficiency ( Abascal and Baldassarri, 2015 ; Nikolakis and Nelson, 2019 ; Uslaner). These outcomes reciprocally boost citizens' general, specific, and political trust ( Nikolakis and Nelson, 2019 ; Watkins, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional and policy context IFM was prohibited (and often displaced) over large areas (Ritchie 2009, Minor andBoyce 2018), particularly where Indigenous peoples were removed from their lands and resources, and forbidden from practicing their culture and language (Nikolakis 2019, Nikolakis and Nelson 2019). The emergence of IFM as a "legitimate" alternative to fire suppression involves a reactivation of Indigenous knowledge and enhanced participation in land governance (Whitehead et al 2008.…”
Section: The United Nations Sendai Framework For Disaster Riskmentioning
confidence: 99%